2022
DOI: 10.1101/2022.02.07.478973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FGF8 induces chemokinesis and regulates condensation of mouse nephron progenitor cells

Abstract: Kidneys develop via iterative branching of the ureteric epithelial tree and subsequent nephrogenesis at the branch points. Nephrons form in the cap mesenchyme as the metanephric mesenchyme (MM) condenses around the epithelial ureteric buds (UBs). Previous work demonstrated that FGF8 is important for the survival of nephron progenitor cells (NPCs), and early deletion of Fgf8 leads to the cessation of nephron formation, which results in post-natal lethality. We now reveal a novel function of FGF8. By combining t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Similarly, Fgf9 and Fgf20 are expressed in NPs and have established roles in survival and self-renewal. Another recent study highlighted the significant chemokinetic effect of FGF8 and its importance in the condensation of nephron progenitor cells around the ureteric tip (Sharma et al 2022). Specifically, when Fgf8 was deleted in Wnt4 positive cells, it resulted in smaller kidneys, fewer nephrons, and disorganized nephron progenitors, which is consistent with the findings of the present study in the absence of Wnt4 in the niche.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Fgf9 and Fgf20 are expressed in NPs and have established roles in survival and self-renewal. Another recent study highlighted the significant chemokinetic effect of FGF8 and its importance in the condensation of nephron progenitor cells around the ureteric tip (Sharma et al 2022). Specifically, when Fgf8 was deleted in Wnt4 positive cells, it resulted in smaller kidneys, fewer nephrons, and disorganized nephron progenitors, which is consistent with the findings of the present study in the absence of Wnt4 in the niche.…”
Section: Discussionsupporting
confidence: 92%
“…However, Wnt4 and co-expressed signals like Fgf8 and Bmp4 are expressed in multiple cell types in the kidney or early embryo (Sharma et al 2022;Mills et al 2017;Oxburgh et al 2005;Oxburgh et al 2004), confounding conclusions about how their expression in the early committing nephron might affect the niche (Grieshammer et al 2005;Perantoni 2005;Gerber et al 2009;Mills et al 2017;Oxburgh et al 2005;Oxburgh et al 2004). For example, Wnt4 is expressed prior to development of the metanephric kidney, with lineage tracing experiments showing contributions to all major progenitor cell types (Lawlor et al 2019;Park et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…WNT4 is necessary for PTA formation [37], and by itself sufficient to trigger a mesenchymal-to-epithelial transition and subsequent tubulogenesis, although other members of the WNT family (WNT1, WNT3a, WNT7a, WNT7b, but not WNT11) can substitute for WNT4 [17]. WNT4 and the fibroblast growth factor FGF8 engage in a positive feedback by supporting each other’s expression, but FGF8 supports RV formation also independent of WNT4 [30, 33]. WNT9b induces RV formation by counteracting the transcription factor SIX2, which supports its own expression, and prevents the differentiation of nephron progenitor cells (NPC) by repressing PTA markers such as Wnt4 and Fgf8 [29].…”
Section: Introductionmentioning
confidence: 99%
“…WNT4 is necessary for PTA formation [59], and by itself sufficient to trigger a mesenchymal-to-epithelial transition and subsequent tubulogenesis, although other members of the WNT family (WNT1, WNT3a, (B) WNT7a, WNT7b, but not WNT11) can substitute for WNT4 [28]. WNT4 and the fibroblast growth factor FGF8 engage in a positive feedback by supporting each other’s expression, but FGF8 supports PTA formation also independently of WNT4, in part by increasing cell motility [47, 55]. Cell tracking revealed that NPCs move largely stochastically in the CM, and cells that initiate Wnt4 expression can still return to the Six2 -positive progenitor pool [7, 33, 35].…”
Section: Introductionmentioning
confidence: 99%